The two orders of governance failure: Design mismatches and policy capacity issues in modern governance. Issue 4 (1st December 2014) - Howlett, M; Ramesh, M
Abstract: Perceptions of the pervasive and persistent failures of governments in many issue areas over the past several decades have led many commentators and policy makers to turn to non-governmental forms of governance in their efforts to address public problems. During the 1980s and 1990s, market-based governance techniques were the preferred alternate form to government hierarchy but this preference has tilted towards network governance in recent years. Support for these shifts from hierarchical to non-hierarchical governance modes centre on the argument that traditional government-based arrangements are unsuited for addressing contemporary problems, many of which have a cross-sectoral or multi-actor dimension which is difficult for hierarchies to handle. Many proponents claim that recent 'network governance' or 'collaborative governance' arrangements combine the best of both governmental and market-based alternatives by bringing together key public and private actors in a policy sector in a constructive and inexpensive way. This claim is no more than an article of faith, however, as there is little empirical evidence supporting it. Indeed both logic and evidence suggests that networks too suffer from failures, though the sources of these failure may be different from other modes. The challenge for policymakers is to understand the origin and nature of the ways in which different modes of governance fail so that appropriate policy responses may be devised. This article proposes a model of such failures and a two-order framework for understanding them which helps explain which mode is best, and worst, suited to which circumstance.